Privatization Trends - Kikeri, Sunita; Phipps, Verena (World Bank, Washington, DC, 2012)
This note is based on a World Bank Group database that uses transaction values as a proxy for measuring privatization trends. It includes only the values resulting from the full or partial sale, concession, lease, or initial public offering of existing state owned enterprises or other government assets. An update of the World Bank Group's Privatization Database shows that privatizations in developing countries amounted to US$70 billion in 2006 or US$105 billion including two mega Chinese offerings. Both results beat all previous years in nominal terms. Contrary to popular perceptions of a slowdown, the data show that privatization in its various forms continued in a broad range of countries and sectors, particularly infrastructure and banking. Initial public offerings were prominent, especially in China.